Sporazumevanje - nov predmet na Medicinski fakulteti v Ljubljani - Petek Šter, Marija (Zdravniški vestnik, 2011)
Changes of curriculum in medicine and dental medicine at the Medical Faculty Ljubljana according to Bologna declaration has been started in the academic year 2009/10. New curriculum at the Medical Faculty of Ljubljana introduced early clinical exposure for first-year medical students through the subject ĆCommunicationĆ. Our aim is to present the outline and the contents of the newsubject and point out our experiences and dilemmas. The decision for introducing this subject is based on the empirical recognition of the fact that previous programme lacked the necessary knowledge and experience for goodinterpersonal communication. With early clinical exposure we want to achieve several aims: providing students with the basic knowledge on medical psychology, teach them how to communicate with healthy people and patients, present them the rules for communication within a small group and help them understand that a good doctor-patients relationship is crucial for successful treatment.
Keywords: education; izobraževanje; Medicinska falkulteta; sporazumevanje